A randomized double-blind study to evaluate asurgeon-based technique to reduce post-operative pain in minimal gynecological surgery - Mustafa, Asif; Khemani, Manju; Verma, Deepika; Chandra Kapoor, Mukul; Makhija, Bela; Bhandari, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study aims to evaluate whether instillation of levo-bupivacaine intraperitoneally decreases post-operative pain after laparoscopic gynaecological surgeries, using VAS pain Scale. Methods: Randomized placebo controlled double blinded study conducted at tertiary care hospital in New Delhi. 90 ASA I & II women scheduled to undergo elective laparoscopic gynaecological surgeries. 20 ml 0.5% levo-bupivacaine diluted with 40ml normal saline (total 60ml) intraperitoneally at the end of surgery before closure of ports along with port site infiltration of levo-bupivacaine (3-5 ml) in intervention group and 60 ml normal saline intraperitoneally in control group. Results: Mean pain scores were significantly lower (p<0.01) in the intervention group when compared to the control group for initial 4 hours of the study after that mean pain score was lower in intervention group than control group but it was statistically not significant. The requirement of rescue analgesia was also significantly lesser in intervention group compared to control group. Conclusions: Levo-bupivacaine is an easy, cheap and non-invasive method which provides good analgesia in the immediate postoperative period after laparoscopic gynaecological surgery, without adverse effects, especially in the early postoperative period. This improves patients experience and should be made an integral part of all minimal gynaecological endoscopic surgery.